Highly porous and easy shapeable poly-dopamine derived graphene-coated single walled carbon nanotube aerogels for stretchable wire-type supercapacitors. (April 2018) - Zhou, Gengheng; Kim, Na-Ri; Chun, Sang-Eun; Lee, Wonoh; Um, Moon-Kwang; Chou, Tsu-Wei; Islam, Mohammad F.; Byun, Joon-Hyung; Oh, Youngseok
Abstract: Easy shapeable highly porous and robust three dimensional (3D) nano-carbon architectures (3D NCA) are crucial for the practical applications of electrochemical energy storage devices. Here, a facile easy shapeable nitrogen-doped graphene coated 3D NCA exhibiting an ultra-high specific surface area, remarkable robustness, and excellent aqueous wettability is reported. A 3D single-walled carbon nanotube (SWCNT) hydrogel composed of isolated SWCNTs is first prepared, and then a thin polydopamine (pDA) layer is uniformly coated onto the fabricated 3D SWCNT hydrogel via an in situ polymerization of dopamine. A nitrogen-doped graphene-coated 3D NCA is obtained via pyrolysis of the pDA-coated 3D NCA. By decorating this highly porous nitrogen-doped 3D NCA onto helical micro carbon fibers, a highly stretchable (∼100% strain) wire-type supercapacitor (WTSC) is fabricated. The areal specific power and energy density of the WTSC are determined to be 2.59 mW cm −2 and 1.1 μWh cm −2, respectively. These values are remarkably larger than those previously reported WTSCs. Moreover, our WTSC maintains more than 91% of its capacitance after 10, 000 stretch-release cycles at tensile strains of up to 50%. The combination of the easy shapeable, robust and highly porous nitrogen-doped 3D NCA paves a new way for the development of high-performance wearable textile-based energy devices. Graphical abstract: A nitrogen-doped graphitic layer-coated 3D NCA exhibiting an ultra-high SSA, remarkable mechanical robustness, and excellent aqueous wettability was produced. A WTSC with electrodes made from μCFs decorated by this 3D pDA-Gr NCA was also fabricated by helically wrapping around a PU wire; this WTSC exhibits an ultra-high capacitance, high energy density, and excellent stability under tensions of up to 100% strain. Image